32.4k views
0 votes
PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!!

Solve.

x^2 − 9x + 3 = 0

PLEASE HELP ASAP!!! CORRECT ANSWER ONLY PLEASE!! Solve. x^2 − 9x + 3 = 0-example-1
User Bisgardo
by
6.2k points

1 Answer

2 votes


given \: equation: {x}^(2) - 9x + 3 = 0 \\ \\ x = \frac{ - b \pm \sqrt{ {b}^(2) - 4ac} }{2a} \\ \\ x = \frac{ 9 \pm \sqrt{ {( - 9)}^(2) - 4 * 1 * 3} }{2 * 1} \\ \\ x = (9 \pm √(81 - 12) )/(2) \\ \\ x = (9 \pm √(69) )/(2) \\ \\ x = (9 + √(69) )/(2) \: \: and \: \: (9 - √(69) )/(2)
User Turong
by
6.2k points